Increasing mother’s knowledge through “Isi Piringku” education as an effort to prevent stunting among toddlers in Sungai Tuan Ulu Village, Banjar Regency - Filia Sofiani Ikasari; Iis Pusparina; Dewi Irianti (Community Empowerment, 2022)
Banjar Regency in South Kalimantan Province ranks first for the Regency with a significant increase in stunting cases. One of the government's efforts to prevent stunting is to promote education about "Isi Piringku". The purpose of this community service is to increase the knowledge of mothers in Sungai Tuan Ulu Village about "Isi Piringku" to prevent stunting. The educational method given to the mother is a two way method, namely question and answer using flip chart media. This method allows the mother to discuss with the team during the program. This program succeeded in providing understanding to partners about the importance of applying "Isi Piringku" to toddlers.